FORMULATION AND STABILITY TESTING OF NATURAL SUNSCREEN WITH DIFFERENT ESSENTIAL OILS AGAINST Escherichia coli (E. coli) - Rodzi, Siti Zairyn Fakurol; Moorthy, Mahaganesh; Suriadi, Rokiah; Emilia, Sharifah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
The widespread use of synthetic sunscreen agents such as oxybenzone and avobenzone has raised significant environmental and health concerns, including coral reef bleaching and potential endocrine disruption. In response, this study aims to formulate a natural sunscreen incorporating essential oils with known antimicrobial properties, and to evaluate the antibacterial effectiveness of each formulation against Escherichia coli (E. coli). Three formulations were developed using tea tree oil (Melaleuca alternifolia), lavender oil (Lavandula angustifolia), and peppermint oil (Mentha piperita) at a concentration of 2% (w/w), with zinc oxide (20% w/w) serving as the physical UV blocker. All samples were tested using the agar well diffusion method, and the zones of inhibition were measured after 24 hours of incubation at 37°C to assess antibacterial activity. Preliminary findings suggest that tea tree oil exhibits the strongest inhibition zone against E. coli, while peppermint oil showed limited or negligible antibacterial effects. This study contributes to the growing body of research on natural cosmeceutical alternatives and supports the advancement of microbiologically stable, plant-based sunscreen formulation.